2020
DOI: 10.3390/md18090444
|View full text |Cite
|
Sign up to set email alerts
|

Sargassum fusiforme Polysaccharides Prevent High-Fat Diet-Induced Early Fasting Hypoglycemia and Regulate the Gut Microbiota Composition

Abstract: A low fasting blood glucose level is a common symptom in diabetes patients and can be induced by high-fat diet (HFD) feeding at an early stage, which may play important roles in the development of diabetes, but has received little attention. In this study, five polysaccharides were prepared from Sargassumfusiforme and their effects on HFD-induced fasting hypoglycemia and gut microbiota dysbiosis were investigated. The results indicated that C57BL/6J male mice fed an HFD for 4 weeks developed severe hypoglycemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…Our recent study reported that five S. fusiforme polysaccharides prepared through hot-water and acid extraction showed a wide range of molecular weight (10-698.3 kDa), and the HCl-extracted polysaccharide (Sf-A) mainly consisted of glucose, fucose, and galactose [16]. Cheng et al prepared a 205.8 kDa S. fusiforme polysaccharide (SFF) by acid extraction and the polysaccharide was mainly composed of fucose and galactose [17].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Our recent study reported that five S. fusiforme polysaccharides prepared through hot-water and acid extraction showed a wide range of molecular weight (10-698.3 kDa), and the HCl-extracted polysaccharide (Sf-A) mainly consisted of glucose, fucose, and galactose [16]. Cheng et al prepared a 205.8 kDa S. fusiforme polysaccharide (SFF) by acid extraction and the polysaccharide was mainly composed of fucose and galactose [17].…”
Section: Discussionmentioning
confidence: 99%
“…Seaweed polysaccharides represent a kind of promising natural product that alleviates HFD-induced metabolic syndrome and promotes the healthy growth of gut bacteria [12]. In recent years, polysaccharides prepared from Sargassum fusiforme, a well-known edible alga, have attracted extensive research interest due to their potential biomedical application [13][14][15][16][17]. For example, our recent study indicated five polysaccharides prepared from S. fusiforme could selectively regulate the relative abundance of Oscillospira and Clostridiales in cecal microbiota of HFD-fed mice [16].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations